A new South American species of Centris (Heterocentris) Cockerell, 1899 with a key to the species with horn-like projections on the clypeus (Hymenoptera: Apidae: Centridini) - Vélez, Danny; Vivallo, Felipe (Zootaxa, 2012)
The genus Centris Fabricius, 1804 is one of the more diverse lineages of solitary bees in the Neotropical Region with more than250 described species. Here Centris ceratops new species is described from a tropical dry forest in northern Colombia (Colosó,Department of Sucre), thus increasing the number of known species to four in which the females possess a horn-like projectionon the clypeus. This group of bees belongs to a small monophyletic group within C. (Heterocentris). Along with the description of this new species, diagnosis, pictures and a key to identify the species of females with modified clypeus are also provided.